2019
DOI: 10.1111/tbj.13657
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of BioZorb implantable device in breast‐conserving surgery

Abstract: BioZorb fiducial marker is an implantable device made of six clips to mark the surgical site of tissue removal in three dimensions. The marker facilitates focused radiation therapy, while allowing for tissue ingrowth during the healing process with resorption by the body overtime. Current literature investigating the use of the BioZorb is limited and focused on its value for radiation treatment. Our objective was to investigate the feasibility and surgical complications associated with the BioZorb in breast-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…There is currently a paucity of data related to the surgical complications secondary to use of a BioZorb. Reported complications seem to be minor and occur rarely 3,4 . However, our patient went on to complete post‐lumpectomy radiation for her DCIS, and nearly 9 months later presented with chronic symptoms of breast infection, pain, erythema, and ultimate erosion of the BioZorb through her skin 1 year after initial surgery.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There is currently a paucity of data related to the surgical complications secondary to use of a BioZorb. Reported complications seem to be minor and occur rarely 3,4 . However, our patient went on to complete post‐lumpectomy radiation for her DCIS, and nearly 9 months later presented with chronic symptoms of breast infection, pain, erythema, and ultimate erosion of the BioZorb through her skin 1 year after initial surgery.…”
Section: Discussionmentioning
confidence: 82%
“…Another single‐institution study from Chung and Srour concluded that the BioZorb was safe to use due to the rarity of complications. In this series, only 2 of 91 patients had the BioZorb removed (one at time of re‐excision of positive margins secondary to discomfort and one that had migrated to the axilla, requiring explant) 4 . To date, there have been no reported events of postoperative erosion of the BioZorb device into the NAC requiring removal and debridement of the breast.…”
Section: Introductionmentioning
confidence: 94%
“…There is a "learning curve" for effective use of this device. The re-absorption can take up to two years with persistence of a palpable presence of the device at the tumor site, but with careful sizing of the implant this has rarely been an issue (55). Most of our patients have In some cases, we found the partial restoration in lost tissue volume to markedly improve the cosmetic outcome (e.g., upper inner and medial breast).…”
Section: Biozorbmentioning
confidence: 81%
“…A recent single-center study of 89 patients implanted with the BZ found that the BZ still was palpable at the time of the last clinical breast exam (performed at a median 1.1 years) for 63.6 % of the patients, with palpability observed to persist as late as 2.8 years after implantation. 36 Followup datapoints collected in the registry with relevance to device palpability are limited to the event-reporting of pain, which occurred for 1.1 % of the patients and was concentrated in the first 3 months after BCS, with reported reasons for device removal. Only two patients (0.2 %) requested device removal due to pain or anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…This marker has been associated with positive cosmetic and overall patient outcomes as well as reduced RT volumes in the few reported studies to date. [36][37][38][39][40][41][42] These studies have been small, focused on RT planning outcomes or limited to short-term follow-up evaluation. This is the first report of 24-month outcomes after BCS with BioZorb Ò (BZ) implantation in a large U.S. registry of data collected across an array of clinical settings.…”
mentioning
confidence: 99%